Community Service to Increase Patient Awareness in Osteoarthritis Disease Prevention at Ibnu Sina Hospital, Panakukang District Makassar - Dhedie Prasatia Sam, Andi; Mula Putra, Fadil (Al Makki Publisher, 2024)
This study aimed to investigate the relationship between Presbycusis, Elderly, Osteoarthritis Audiometry, and risk factors such as obesity, lack of physical activity, and injury to the joints. The research method used was a survey using questionnaires distributed to the elderly at Ibnu Sina Hospital, Panakkang District, Makassar. The results showed a significant correlation between the conditions of presbycusis, osteoarthritis, and the mentioned risk factors. The implication of this research is the importance of increasing public awareness and knowledge of osteoarthritis prevention and management through targeted and interactive education, such as using banners that are easy to understand and involve direct discussions with the community. This is expected to reduce the incidence of osteoarthritis and reduce the burden of medical costs and improve the quality of life of the elderly.